Indonesian Government Budgeting: A Bibliometric Analysis - Oktaviyani, Tri (International Journal of Advanced Multidisciplinary, 2023)
One of the important processes in financial management is budgeting. It is also needed in the Indonesian government's financial system. So far, there have been many previous studies that have addressed the topic of budgeting in the Indonesian government's financial system. However, there have been no studies involving developmental research on the Indonesian government on a global scale. This study aims to fill this gap. This research type is desk research. Bibliometric analysis was used in this study. The data source analyzed is the Scopus database. The results found that research on Indonesian Government Budgeting has been present since 1993. The total number of articles discussing this topic up to July 4th, 2023, was 113 articles. The most publications occurred in 2020. The most prolific authors were Kahar, S.H.A., and Prabowo, T.K.W., with each producing 3 articles discussing Indonesian government budgeting. The most productive journals was the IOP Conference Series: Materials Science and Engineering. Indonesian government budgeting was most widely discussed in the field of Social Sciences. The title of the most cited article was 'Can Indonesia Succeed in Decentralization? Plans, Problems, and Prospects,' published in Bulletin of Indonesian Economics (2021) and written by the Alm J., Aten R.H., and Bahl R. The journal is also the most cited source.